A Critical Analysis of “A Short Guide to Writing about Film” - ali sheikhmehdi; Arsalan Moghadas (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book, A Short Guide to Writing about Film, is a description of how to analyze movies. The book closely linked to thinking about film and writing about it. To achieve this goal, the author focuses on defining the terminology and professional concepts of cinema as well as movie analysis approaches. For analysis and critique, it is necessary to have a theoretical plan to carefully analyze the movies, but the described approaches in this book, are not the main movie analysis approaches, and for instance, approaches like formalism and ideology lack a theoretical basis. More specifically, in this book, formalism is considered the same as structuralism.